Nuevos regionalismos : °cooperación o conflicto? / Lincoln Bizzozero, Klaus Bodemer, Marcel Vaillana, editores - Bizzozero, LincolnBodemer, KlausVaillant, Marcel
"The first section of this excellent collection of articles places Mercosur in the larger context of new regional agreements and the transformations in multilateral trade arrangements associated with the Uruguay Round of GATT. Other sections address the specific nature and prospects of the relations between Mercosur, the EC and the US. Authors explore from the Southern Cone perspective, the tensions between multilateralism vs. regionalism in an attempt to present the different commercial strategic options open to these countries in the 1990s"--Handbook of Latin American Studies, v. 57.Trabajos presentados al seminario "Nuevos regionalismos: cooperación o conflicto? rel MERCOSUR y el sistema internacional," organizado por el Programa de Investigación en Integración Regional, Universidad del República del Uruguay, Sept. 14-15, 1993.